The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1007/bf01753418
|View full text |Cite
|
Sign up to set email alerts
|

Actin-attached and detached crossbridges in myofibrils: Segregation into two populations according to their sensitivity to proteolytic digestion of myosin heavy chain

Abstract: Tryptic digestion of myofibrils was used to assess the interaction of crossbridges with thin filaments in the presence of ATP analogues. The relative amounts of 200 kDa fragment produced by trypsin from myosin heavy chain when the crossbridge is attached to actin, and of 160 kDa fragment produced when the crossbridge is detached from actin, served as a measure of crossbridge-actin interaction. In rigor only the 200 kDa fragment was produced suggesting that a great majority of the crossbridges were strongly att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Attachment of myosin to actin also decreases the susceptibility to proteolysis of a region of the myosin head in the vicinity of residues 640-650. This susceptibility is partially restored in the presence of MgPPi or MgAMPPNP, with estimates of the fraction of heads dissociated in rough agreement with those found here and by Fajer et al (Chen and Reisler, 1984;Assulin et al, 1986). MgPP; binds strongly to myosin (Kd 0.5 ,tM) but only weakly to the actomyosin complex, Kd 2-4 mM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Attachment of myosin to actin also decreases the susceptibility to proteolysis of a region of the myosin head in the vicinity of residues 640-650. This susceptibility is partially restored in the presence of MgPPi or MgAMPPNP, with estimates of the fraction of heads dissociated in rough agreement with those found here and by Fajer et al (Chen and Reisler, 1984;Assulin et al, 1986). MgPP; binds strongly to myosin (Kd 0.5 ,tM) but only weakly to the actomyosin complex, Kd 2-4 mM.…”
Section: Discussionsupporting
confidence: 91%
“…These changes could be due to either an actomyosin bond with altered mechanical properties or to cross-bridge detachment, or to both effects. The possibility of cross-bridge detachment has received support from combined stiffness and x-ray diffraction measurements in fibers (Brenner et al, 1986b) as well as proteolytic digestion experiments on myofibrils (Chen and Reisler, 1984;Assulin et al, 1986). Other studies using intact fibers, x-ray diffraction, and electron microscopy have clearly shown that MgAMPPNP produces changes in cross-bridge structure upon binding (Goody, et al, 1976;Lymm, 1975;Marston et al, 1976;Padron and Huxley, 1984;Reedy et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Conformational changes in the actin filament due to the binding of S-l have been reported by Ando (1989). Evidence that not all myosin heads are optimally activated in myosin filaments comes from a lower Kmax for myosin filaments than for S-l (Pope et al, 1981 fibers also indicate at least two populations of myosin heads seeing different effective actin concentrations (Assulin et al, 1986; Pate & Cooke, 1988;Fajer et al, 1988). These results suggest that the mechanism of increasing myosin activity in the filament may involve at least two processes: recruitment of myosin heads which are inaccessible to the actin filament and increased activation of myosin heads which are already exposed to actin.…”
Section: Discussionmentioning
confidence: 77%